CHARACTERISTICS AND THE OUTCOME OF VERY LOW BIRTH WEIGHT INFANT BORN IN SANGLAH HOSPITAL DENPASAR - Putra, Yoga; Kardana, Made; Artana, Dharma; Putra, Junara (Medicina; Vol 43 No 2 (2012): Mei 2012, 2013)
Very low birth weight (VLBW) infants is one of the most important medical problem especially in developing countries. This issue is due to its high morbidity and mortality rate. On the other hand, the long term impact of VLBW infants are poor growth and development including physical, emotional, intelectual (IQ), and disabilities, therefore it could decrease the quality of human resources and become a burden to their family. The objective of this study was to describe the characteristics and outcome among VLBW infants born in the Sanglah Hospital. This was a retrospective study. Data were collected from medical record of all infants with VLBW delivered in Sanglah Hospital from January to Desember 2009. Uncompleted infants and mother medical records were excluded from this study. Of 64 VLBW infants enrolled into the study of which 54.7%  of this subjects was male, median of weight was 1300 g, mean gestational of age was 30.9 (SD 2.28) weeks, and mean lenght of stay was 30.9 (SD 19.7) days. The survival of VLBW infants in this study was 62.5%,  mortality in the early neonatal period was 70,8%. The percentage of VLBW infants who survive was still low and the major causes mortality were HMD (50%) and sepsis (41.6%). The mortality of VLBW happened mostly in early neonatal periode.
Keywords: very low birth weight, outcome